ANALISIS ASOSIASI MEREK TERHADAP RESPON KONSUMEN PADA MEREK HEDONIK - Henryanto Abaharis (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2015)
This study was intended to test the brand association to consumer response at hedonic brand. Especially on the effect of dimensions brand function (guarantee function, personal identification function, social identification function, and status function) to consumer response (brand extension, recommendation and consumer willingness to pay at price premium). The model of this research is firstly advanced by Bele’n del Rio et al., (2001) in his article entitled “The effects of brand functions on consumer response”. The subjects of this study were193 students to hedonic brand who lived in Daerah Istimewa Yogyakarta (DIY). By using analysis instrument of Structural Equation Modeling in AMOS 4.01 program. The results of the analysis suggested on the hedonic brand had effects of dimensions brand function to consumer response, especially on personal identification and social identification. Keywords: Dimensions brand function, brand extension, recommendation, price premium, hedonic brand